Incorporating carboxymethyl cellulose into microfibrillated cellulose for barrier coating to delay banana browning and extend shelf life - Jing Geng; Nicole Stark; Peter Kitin; Xiao Zhang; Nayomi Z. Plaza; J.Y. Zhu (Food Chemistry, 2025)

Microfibrillated cellulose (MFC) barrier coating for extending banana shelf life - Jing Geng; Jane O'Dell; Nicole Stark; Peter Kitin; Xiao Zhang; J.Y. Zhu (Food Hydrocolloids, 2024)

Characterizing lignin-containing microfibrillated cellulose based on water interactions, fibril properties, and imaging - Xiaoxue Zhang; Peter Kitin; Umesh P. Agarwal; Rolland Gleisner; J.Y. Zhu (Carbohydrate Polymers, 2023)

Climate change and the regulation of wood formation in trees by temperature - Shahanara Begum; Kayo Kudo; Md Hasnat Rahman; Satoshi Nakaba; Yusuke Yamagishi; Eri Nabeshima; Widyanto Dwi Nugroho; Yuichiro Oribe; Peter Kitin; Hyun-O Jin; Ryo Funada (Trees, 2018)

Cambial dormancy induced growth rings in Heritiera fomes Buch.- Ham.: a proxy for exploring the dynamics of Sundarbans, Bangladesh - Md. Qumruzzaman Chowdhury; Peter Kitin; Maaike De Ridder; Claire Delvaux; Hans Beeckman (Trees, 2016)

Spatial mapping of extracellular oxidant production by a white rot basidiomycete on wood reveals details of ligninolytic mechanism - Christopher G. Hunt; Carl J. Houtman; Don C. Jones; Peter Kitin; Premsagar Korripally; Kenneth E. Hammel (Environmental Microbiology, 2013)
Summary Oxidative cleavage of the recalcitrant plant polymer lignin is a crucial step in global carbon cycling, and is accomplished most efficiently by fungi that cause white rot of wood. These basidiomycetes secrete many enzymes and metabolites with proposed ligninolytic roles, and it is not clear whether all of these agents are physiologically important during attack on natural lignocellulosic substrates. One new approach to this problem is to infer properties of ligninolytic oxidants from their spatial distribution relative to the fungus on the lignocellulose. We grew P hanerochaete chrysosporium on wood sections in the presence of oxidant‐sensing beads based on the ratiometric fluorescent dye BODIPY 581/591. The beads, having fixed locations relative to the fungal hyphae, enabled spatial mapping of cumulative extracellular oxidant distributions by confocal fluorescence microscopy. The results showed that oxidation gradients occurred around the hyphae, and data analysis using a mathematical reaction–diffusion model indicated that the dominant oxidant during incipient white rot had a half‐life under 0.1 s. The best available hypothesis is that this oxidant is the cation radical of the secreted P . chrysosporium metabolite veratryl alcohol.

A comparative histological study between normal and fasciated shoots of Prunus avium generated in vitro - Peter Kitin; Ivan Iliev; Apostolos Scaltsoyiannes; Christos Nellas; Athanassios Rubos; Ryo Funada (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)